Evolution, forecasting and managment of siltation in Algerian dams - Khentouche, Adel; Bella, Nassim (Italian journal of engineering geology and environment, 2022)
The aim of this study was to improve the sedimentation estimates and to know the evolution of the siltation of 8 Algerian dams according to a semi-quantitative approach which takes into account the comparison of the bathymetric surveys and the calculations carried out by empirical formulas widely used in Algeria (F. Orth). The initial capacity of the 8 considered reservoirs was 906 Mm3, it was reduced to 675.14 Mm3 in 1986 about 524.5 Mm3 in 2010, It is noticed a decrease of 370.5 Mm3 or 58.6% between the initial capacity and the last bathymetric survey in 2010. The average annual siltation is clearly varied according to the following phases: - a weak alluvial phase had started with the impoundment until 1986 and showed less than 0.50 Mm3 of silt; - an average alluvial phase extends between 1986 and 2004 and presents values varying between 0.50 Mm3 and 0.60 Mm3; - a high alluvial phase spread between 2004 and 2010, it gives considerable volumes which annually exceeds 0.60 Mm3. On the other hand, F. Orth model gives results close and comparable to those obtained by bathymetric surveys for most dams, which qualifies the application of this model in similar conditions in the absence of gauging stations.